Bis(chlorogermyliumylidene) and its significant role in elusive reductive cyclization. Issue 77 (10th September 2018) - Majumdar, Moumita; Raut, Ravindra K.; Sahoo, Padmini; Kumar, Vikas
Abstract : Bis(chlorogermyliumylidene) has been obtained within a bis(α-iminopyridine), where the [GeCl] + units conduce elusive reductive cyclization maintaining high stereoselectivity. Abstract : Bis(chlorogermyliumylidene) 2 has been strategically obtained within redox-active bis(α-iminopyridine). Metal-free reduction of 2 followed by protonation led to elusive 2, 3-di(pyridin-2-yl)piperazine with meso -stereoselectivity. Formation of persistent triplet diradicals upon reduction and isolation of piperazine stabilized Ge(ii ) dication intermediates provide convincing evidence for the crucial role of [GeCl] + units in reductive cyclization.